2005
DOI: 10.1159/000082093
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Second Primary Tumors by an Acyclic Retinoid in Patients with Hepatocellular Carcinoma

Abstract: Oral administration with acyclic retinoid, a synthetic vitamin A analog, for a limited period of 12 months (48 weeks) prevented the development of second primary hepatocellular carcinoma (HCC) and also improved the survival of patients who underwent curative treatments of the initial tumor. Following that randomized controlled study reported in 1996 and 1999, we have continued to follow up the patients by medical imaging and blood chemical analyses, and found that the preventive effect of acyclic retinoid last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 33 publications
3
76
0
Order By: Relevance
“…In 1966, Muto et al [407] reported that administration of polyprenoic acid, an acyclic retinoid, reduced recurrence of HCC in an RCT. Updated, long-term data were subsequently published [408], postulating that the eradication of premalignant or latent malignant clones is the mechanism of action. The effect is, however, yet to be confirmed in a large-scale RCT.…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 99%
“…In 1966, Muto et al [407] reported that administration of polyprenoic acid, an acyclic retinoid, reduced recurrence of HCC in an RCT. Updated, long-term data were subsequently published [408], postulating that the eradication of premalignant or latent malignant clones is the mechanism of action. The effect is, however, yet to be confirmed in a large-scale RCT.…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 99%
“…YAC-1 cells, kindly provided by the Cell Resource Center for Biochemical Research, Institute of Development, Aging and Cancer, Tohoku University, were used as target cells. YAC-1 cells (2x10 6 ) were labeled with 3.7 MBq of Na 2 51 CrO 5 (MP Biomedicals, Irvine, CA) at 37˚C for 1 h in a shaking water bath. Labeled target cells were washed with PBS and adjusted to 1x10 5 /ml in a complete medium, then seeded at a concentration of 1x10 4 cells/well in micro-well plates.…”
Section: Animalsmentioning
confidence: 99%
“…Most patients with HCC also suffer from liver cirrhosis, which is the major risk factor for HCC, mainly caused by infection with either the hepatitis B virus (HBV) or the hepatitis C virus (HCV) (2). Ursodeoxycholic acid (3) and glycyrrhizin (4) have been reported to be effective in preventing liver carcinogenesis, while recently the preventive effects of vitamin K2 (5) and acyclic retinoid (6) towards recurrence in patients with HCC have been reported. Nevertheless, HCCs frequently occur in patients with HCV cirrhosis at an annual rate of ~8% in Japan, with recurrence within 5 years seen in 70% of cases (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the human hepatoma cell line HepG2, retinoic acid induces growth arrest and differentiation [20]. The survival rate of patients with hepatocarcinoma was significantly prolonged by a 12-months postoperative treatment with retinoids as adjuvant treatment [21].…”
Section: Introductionmentioning
confidence: 99%